Afghanistan and United States foregin relation after September 11th 2001 - Khurami, Hafiza (Technium Business and Management, 2023)
The incident of 11 September 2001 played an important role the relations between Afghanistan and the United States. After that Afghanistan was the axis of attention to US foreign policy. The US Military presence in Afghanistan has different reason. Afghanistan is a tool for the United States to achieve its goal, because Afghanistan has a special geopolitical position through which it can achieve its ideological goals, one of these reasons could be the struggle against Islam. because the Middle East countries are the cradle of Islam. And the United States considers these countries to be the source of terrorism, which is the enemy of the United States. And to achieve its political goals by establishing military bases in Afghanistan under the influence of powers such as Russia, China and Iran. Afghanistan’s proximity to the Middle East and Central Asia, which are rich in oil and gas resources, is also economically important to the United States. So Afghanistan’s geopolitical position could be a good platform to achieve these US goals.